Sustainable development and nuclear energy -The dialectical relation – - خلف حســام عبد الأمير (Journal of Legal Sciences, 2019)
Today, development is the dominant idea at the international and national levels, while energy is at the heart of development as the engine and vital element of modern civilization, which can’t be achieved without the participation of an energy policy that takes into account this concern. At the same time, we can’t make any development in the margins of human rights, in other words, if we are to move to development, it would be wise to do so taking into account the rights of present and future generations, whereas they provide the greatest amount of development and less environmental damage. This may not be possible for all energy options, including nuclear, because of its intersection with the rights of future generations.